MTHFR gene polymorphisms and response to chemotherapy in colorectal cancer: a meta-analysis. (August 2009) - Zintzaras, Elias; Ziogas, Dimitrios C; Kitsios, Georgios D; Papathanasiou, Afroditi A; Lau, Joseph; Raman, Gowri
Aims: Pharmacogenetic studies investigating the relationship between MTHFR gene polymorphisms and response to fluorouracil-based chemotherapy in patients with colorectal cancer have produced inconclusive results. In an attempt to interpret these results, a meta-analysis of all eligible studies published up until January 2009 was carried out.Materials & methods: A total of ten studies relating MTHFR C677T and six studies relating MTHFR A1298C to the response to chemotherapy in patients with colorectal cancer were included in the meta-analysis and random effects pooled odds ratios were estimated. The heterogeneity between studies, the sources of potential bias and the consistency of genetic effects across ethnicities were explored. Cumulative and recursive cumulative meta-analyses were also performed.Results: For both the C677T and A1298C polymorphisms, the main analysis revealed nonsignificant heterogeneity and a lack of association under the allele contrast, the recessive and dominant models. The subgroup analysis by ethnicity did not change this pattern of results. The lack of stability of the relative change of odds ratio in the recursive cumulative meta-analysis for both polymorphisms indicated the need for more evidence to support a definite lack of association. There was no differential magnitude of the effect in large versus small studies.Conclusion: The available evidence indicates that MTHFR C677T and A1298C gene polymorphisms cannot be considered as reliable predictors of response to fluorouracil-based chemotherapy in patients with colorectal cancer.